Pengaruh Iklan dan Kepercayaan Merek Terhadap Minat Beli Pada E-commerce Lazada - Faisal, Alfi; Indah, Dewi Rosa; Maula, Ziaul (Jurnal Samudra Ekonomika, 2023)
This research aims to determine the influence of advertising and brand trust on purchasing interest in Lazada e-commerce. This research used a sample of 112 respondents with the criteria that the respondents were students at the Faculty of Economics, Samudra University and had seen advertisements or had used Lazada at least once. The basic analysis method uses multiple linear regression, t test, F test and coefficient of determination test (Adjusted R2). The results of this research show Y = 6.005+0.094 X1 + 0.739X2. The results of the t test state that the advertising variable has no significant effect on purchase interest in Lazada e-commerce and the brand trust variable has a positive and significant effect on purchase interest in Lazada e-commerce. The results of the F test state that advertising and brand trust simultaneously have a positive and significant effect on purchasing interest in Lazada e-commerce. The coefficient of determination (Adjusted R2) is 0.325 or 39.6%